Analysis Of Community Marketing As A Competitive Strategy Coffee Shop Business Case Study Doi-Ku Café - Aditya Rahman Ginting; Nurbaiti Nurbaiti; Atika Atika (Community Engagement and Emergence Journal (CEEJ), 2025)
This study aims to analyze the community marketing strategies implemented by DOI-KU Café in building customer loyalty and providing a competitive advantage. Using a descriptive qualitative research method, this study highlights how customer engagement through community activities can increase the emotional bond between customers and coffee shop business owners. The results show that this marketing approach is effective in creating customer loyalty, which is manifested by open communication, regular interactions, and the provision of relevant activities that appeal to the community. In conclusion, community marketing is not only able to maintain customer loyalty but also able to strengthen the position of DOI-KU Café in the midst of competition in the coffee shop business that is increasing significantly.